Optimization of Traveling Salesman Problem with Precedence Constraint using Particle Swarm Optimization - M. F. F., Ab Rashid; N. M. Zuki, N. M.; A. N. M., Rose (JSRAD, 2015)

(untitled)
Traveling salesman problem with precedence constraint (TSPPC) is one of the complex problems in combinatorial optimization. Many researchers have suggested various mechanisms to solve this problem effectively. This work presents a combination of Particle Swarm Optimization (PSO) and Topological Sort approach to optimize TSPPC. The original PSO is designed for continuous problem. Therefore, it is incapable to optimize TSPPC, besides the reason of precedence constraint. The proposed PSO with Topological Sort approach was tested with different size of TSPPC problem. The optimization result showed that it yielded better performance in finding the shortest travelling time in all problem size. This finding is associated with better exploration and solution diversity features in PSO.